Address... - Carrington, Edwin W. ([CCS] [Georgetown]GY, 1995)
Focuses on the role of the Caribbean Development Bank in regional development. Highlights the Bank's contribution to the regional transportation and agricultural sectors. Sees the Bank as having an important role to play in the creation of the CARICOM Single Market and in supporting human resource development. Indicates that CDB will have to assist member states in the diversification away from the few staple activities which dominate their economies.